2016
DOI: 10.1039/c5ay01995h
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polyamidoamino (PAMAM) dendrimers using in-line reversed phase LC electrospray ionization mass spectrometry

Abstract: Generation 3 (G3) PAMAM dendrimers are symmetrical, highly branched polymers widely reported in the scientific literature as therapeutic agents themselves or as carrier scaffolds for various therapeutic agents. A large number of analytical techniques have been applied to study PAMAM dendrimers, but one that has been missing is in-line reversed phase LC electrospray ionization mass spectrometry (RP/LC/ESI/MS). To translate PAMAM dendrimers into therapeutic agents, a better understanding of their purity, stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…The functionalized dendrimers described in this paper must be kept in solution at all times otherwise it is not possible to dissolve them again. Moreover, it has been shown that degradation occurs during storage, freeze–thaw and concentration of terminal amino or hydroxy PAMAM dendrimers, explaining why the commercial product is always sold as a 10% w/w solution . Consequently, compounds cannot be thoroughly dried before NMR recording.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functionalized dendrimers described in this paper must be kept in solution at all times otherwise it is not possible to dissolve them again. Moreover, it has been shown that degradation occurs during storage, freeze–thaw and concentration of terminal amino or hydroxy PAMAM dendrimers, explaining why the commercial product is always sold as a 10% w/w solution . Consequently, compounds cannot be thoroughly dried before NMR recording.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been shown that degradation occurs during storage, freezethaw and concentration of terminal amino or hydroxy PAMAM dendrimers, explaining why the commercial product is always sold as a 10% w/w solution. [43] Consequently, compounds cannot be thoroughly dried before NMR recording. Accordingly, to eliminate traces of MeOH, each sample is evaporated to dryness no more than 1 min, then dissolved twice with 0.8 mL MeOH-d 4 and evaporated.…”
Section: Precautions For Handling Dendrimersmentioning
confidence: 99%
“…These commercially available scaffolds are biodegradable and biocompatible [3], with long shelf-life and simple synthetic protocols and they fulfill all the necessary criteria for future technological breakthroughs in the field of biomedicine. They are definitely a viable alternative to the popular polyamidoamine (PAMAM) dendrimers [4,5], especially in light of recent reports detailing poor shelf-life [6] and high inherent toxicity [3,7,8]. The excellent features of monodisperse bis-MPA dendrimers and dendrons have led to their exploitation as precision polymers in an array of potential applications [9,10], for instance, as drug delivery carriers [11], self-assembled monolayers on gold nanoparticles [12], highly structured honeycomb films [13,14], functional hydrogels [15,16] and soft tissue-adhesives [17].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used assays for this are high-performance liquid chromatography (HPLC), mass spectrometry, capillary electrophoresis (CE), polyacrylamide gel electrophoresis (PAGE), and small-angle neutron scattering (SANS). [50][51][52][53] HPLC is a technique that helps identify and quantify the separate components of a mixture or solution. 50 The mixture is dissolved in a liquid solvent and pumped through a column containing a solid adsorbent material.…”
mentioning
confidence: 99%
“…It can be used on both pure samples and mixtures. 51 Capillary gel electrophoresis (CE) is an electro-kinetic method for separating analytes by ionic mobility. It is typically used to characterize low generation dendrimers, yet becomes problematic when characterizing later generations, due to their similarities in charge density and interactions with the wall of the capillary.…”
mentioning
confidence: 99%